دور الخدمات العامة الاجتماعية في تحقيق التنمية البشرية في الجزائر: دراسة تحليلية في الفترة من 1990-2019 - شيخ, محمد (جامعة الوادي University of Eloued, 2021)
هدفت هذه الدراسة إلى التعرف على مدى مساهمة الخدمات العامة الاجتماعية (خدمات التعليم والصحة) في تحسين مؤشرات التنمية البشرية، من خلال تقييم فعالية الانفاق الحكومي على هذه الخدمات باعتبارها آداة رئيسية من أدوات التنمية البشرية وهذا بالاعتماد على المنهج الوصفي التحليلي، توصلت الدراسة من خلاله إلى أنه قد ساهم في تحسين كبير للمؤشرات الكمية لمركبات التنمية البشرية (معدلات الالتحاق وعدد المنشآت القاعدية،.. إلخ) وتحسن جزئي في المؤشرات النوعية (جودة الخدمات المقدمة) ولكن تبقى الخدمات العامة الاجتماعية هي أحد أهم الاستراتيجيات الفعالة لتحقيق الأهداف الاجتماعية للدولة فهي تلعب دورا مهما في تحقيق العدالة الاجتماعية بين أفراد المجتمع وتحسين مؤشرات التنمية البشرية. This study aimed to identify the extent of the contribution of social public services (education and health services) to improvinghuman development indicators, by evaluating the effectiveness of government spending on these services as a major tool for human development, and this is based on the descriptive and analytical approach, through which the study concluded It has contributed to a significant improvement in the quantitative indicators of the components of human development (enrollment rates, the number of grassroots establishments, etc.) and a partial improvement in the qualitative indicators (the quality of services provided), but social public services remain one of the most effective strategies for achieving the state's social goals, as they play an important role In achieving social justice among community members and improving human development indicators.
The role of social public services in achieving human development in Algeria -an analytical study in the period from 1990-2019 -
مقال
Keywords: الخدمات العامة الاجتماعية ; التنمية البشرية ; الصحة ; التعليم; Social public services ; human development ; health ; education